2015
DOI: 10.7326/m15-0308
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Clinical Outcomes of Adding Dipeptidyl Peptidase-4 Inhibitors Versus Sulfonylureas to Metformin Therapy in Patients With Type 2 Diabetes Mellitus

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 37 publications
11
79
1
3
Order By: Relevance
“…Comparable efficacy between gliptins and sulfonylureas when either is added to metformin has been proved in different meta-analyses 2628. In terms of safety related to risk of hypoglycemia, cardiovascular events, and weight gain, gliptins score over sulfonylureas when used both as monotherapy or as add-on to ongoing metformin therapy 26,29. Most patients (53.61%) were on three or more antidiabetic drugs indicating that patients had had the disease for a significant duration.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable efficacy between gliptins and sulfonylureas when either is added to metformin has been proved in different meta-analyses 2628. In terms of safety related to risk of hypoglycemia, cardiovascular events, and weight gain, gliptins score over sulfonylureas when used both as monotherapy or as add-on to ongoing metformin therapy 26,29. Most patients (53.61%) were on three or more antidiabetic drugs indicating that patients had had the disease for a significant duration.…”
Section: Discussionmentioning
confidence: 99%
“…It is validated by the Taiwan National Health Research Institutes for research purposes [18]. This database represents most of the population of diabetic mellitus patients in Taiwan, with a sample of total 1,200,000 patients diagnosed with diabetes since 1999 [19]. It consists of deidentified secondary data for patient’s privacy protection.…”
Section: Methodsmentioning
confidence: 99%
“…Although the addition of an SU is the most common step after metformin fails, these agents have been associated with hypoglycemia, sometimes requiring hospitalizations, particularly in the elderly [10] and in those with polypharmacy [57]. Observational cohort trials have also shown a disadvantage of SUs in general [58, 59], and when compared to DPP-4 inhibitors [60, 61]. …”
Section: Riskmentioning
confidence: 99%